2018
DOI: 10.1534/genetics.117.300499
|View full text |Cite
|
Sign up to set email alerts
|

Coalescent Processes with Skewed Offspring Distributions and Nonequilibrium Demography

Abstract: Nonequilibrium demography impacts coalescent genealogies leaving detectable, well-studied signatures of variation. However, similar genomic footprints are also expected under models of large reproductive skew, posing a serious problem when trying to make inference. Furthermore, current approaches consider only one of the two processes at a time, neglecting any genomic signal that could arise from their simultaneous effects, preventing the possibility of jointly inferring parameters relating to both offspring d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
51
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(53 citation statements)
references
References 74 publications
2
51
0
Order By: Relevance
“…• The other N − U N (z) have one offspring each, Specific modified Moran models leading to Dirac n-coalescents as genealogy limits have been introduced as population models with skewed offspring distributions, see Eldon and Wakeley (2006) and Matuszewski et al (2017), for fixed and variable population sizes. For any Λ-n-coalescent with Λ([0, 1]) = 1 (denoted by Λ ∈ M[0, 1]), Huillet and Möhle (2013, Prop.…”
Section: Models and Main Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…• The other N − U N (z) have one offspring each, Specific modified Moran models leading to Dirac n-coalescents as genealogy limits have been introduced as population models with skewed offspring distributions, see Eldon and Wakeley (2006) and Matuszewski et al (2017), for fixed and variable population sizes. For any Λ-n-coalescent with Λ([0, 1]) = 1 (denoted by Λ ∈ M[0, 1]), Huillet and Möhle (2013, Prop.…”
Section: Models and Main Resultsmentioning
confidence: 99%
“…While some care has to be taken to not change coalescence probabilities (see Remark 4.4 for an example), there will be different possibilities to choose A N,r . For Dirac-n-coalescents with exponential growth (on the coalescent time scale), Matuszewski et al (2017) used A n,r = d N,r . A reasonable approach may also be to set A n,r (close to) proportional to the fraction U Nr /N r of offspring coming from the multiplying parent: Each of the d N,r added individuals are added to the multiplying parent with probability U Nr /N r (with the obvious constraint that after U Nr − 1 individuals are added as offspring of non-reproducing parents, all further individuals need to be added to the multiplying parent).…”
Section: Models and Main Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have demonstrated here that 344 performing inference under the assumptions of the Wright-Fisher model and the 345 Kingman coalescent leads to an incorrect understanding of both population size and 346 selection coefficients in such organisms. Matuszewski et al (2018) have also shown the 347 same to be true for the demographic history of the population. Fortunately, the 348 theoretical details are in place to develop similar inference of demography and selection 349 under biologically appropriate alternative coalescent models (Wakeley, 2013).…”
mentioning
confidence: 79%
“…(2015) demonstrated that population growth may be distinguished from multiple-merger coalescent events owing to progeny-skew, given differing expectations in the SFS. Second, Matuszewski et al . (2018) derived analytical expectations for the SFS under a multiple merger coalescent model with changing population size and further demonstrated that these parameters can indeed be accurately inferred jointly within a likelihood framework.…”
Section: Introductionmentioning
confidence: 99%